The relation between optimum insulation thickness and heating cost on external walls for energy saving - Aytaç, Ayça; Aksoy, U. Teoman (My University, 2006)
In Turkey, the most of the produced energy is used for heating. This situation emphasizes the need for insulation on buildings. In this study, the optimum insulation thickness of the external wall for five different energy-sources (coal, natural gas, LPG, fuel oil, electricity) and two different insulation materials (expanded polystyrene and rock wool) is calculated for Elazi?. Two different wall types as sandwich wall and wall insulated on external side are used in the calculations. As a result, considerable energy saving is obtained. The best results are obtained when coal is used as energy source and expanded polystyrene as insulation material. 4.6 years payback period and 16.359 $/m 2 annual saving are obtained for a wall insulated on external side. 4.2 years payback period and 20.188 $/m 2 saving are obtained for a sandwich wall also.
Enerji? tasarrufu i?çi?n diş duvarlarda opti?mum yalitim kalinli?i ve isitma mali?yeti? i?li?şki?si?
Keywords: Building envelope; Energy saving; Insulation thickness